EFFECT OF BIOINOCULANTS AND FYM ON GROWTH, YIELD AND QUALITY OF SOYBEAN (Glycine max) UNDER RAINFED CONDITIONS OF KASHMIR VALLEY - SINGH, S.R.; Singh, UMMED; SINGH, J.K. (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif seasons of 2004 and 2005 to evaluate the effects of bioinoculants and farmyard manure on performance of rainfed soybean. Sole or dual inoculation of biofertilizers, application of FYM with or without biofertilizers and recommended dose of fertilizer significantly increased plant growth, grain and biological yield, total N, P and K uptake and quality of soybean over control. Application of recommended dose of fertilizer showed markedly higher growth parameters, grain and biological yield, total N, P and K uptake and quality of soybean over rest of the treatments but remain at par with Rhizobium+Azotobacter+PSB+FYM @ 5 t/ha and Rhizobium+PSB+FYM @ 5 t/ha. Among the treatments, maximum oil content in grain, oil yield and protein content and protein yield was recorded with the application of Rhizobium+Azotobacter+PSB+FYM @ 5 t/ha followed by recommended dose of fertilizer and the magnitude of increases were to the tune of 6.9, 9.7, 9.9 and 9.6% over control, respectively.